The Fragility Fracture Postoperative Mobilisation multicentre audit : the reality of weightbearing practices following operations for lower limb fragility fractures - Richardson, C; Bretherton, CP; Raza, M; Zargaran, A; Eardley, WGP; Trompeter, AJ (British Editorial Society of Bone and Joint Surgery, 2022)
Aims The purpose of this study was to determine the weightbearing practice of operatively managed fragility fractures in the setting of publically funded health services in the UK and Ireland. Methods The Fragility Fracture Postoperative Mobilisation (FFPOM) multicentre audit included all patients aged 60 years and older undergoing surgery for a fragility fracture of the lower limb between 1 January 2019 and 30 June 2019, and 1 February 2021 and 14 March 2021. Fractures arising from high-energy transfer trauma, patients with multiple injuries, and those associated with metastatic deposits or infection were excluded. We analyzed this patient cohort to determine adherence to the British Orthopaedic Association Standard, “all surgery in the frail patient should be performed to allow full weight-bearing for activities required for daily living”. Results A total of 19,557 patients (mean age 82 years (SD 9), 16,241 having a hip fracture) were included. Overall, 16,614 patients (85.0%) were instructed to perform weightbearing where required for daily living immediately postoperatively (15,543 (95.7%) hip fracture and 1,071 (32.3%) non-hip fracture patients). The median length of stay was 12.2 days (interquartile range (IQR) 7.9 to 20.0) (12.6 days (IQR 8.2 to 20.4) for hip fracture and 10.3 days (IQR 5.5 to 18.7) for non-hip fracture patients). Conclusion Non-hip fracture patients experienced more postoperative weightbearing restrictions, although they had a shorter hospital stay. Patients sustaining fractures of the shaft and distal femur had a longer median length of stay than demographically similar patients who received hip fracture surgery. We have shown a significant disparity in weightbearing restrictions placed on patients with fragility fractures, despite the publication of a national guideline. Surgeons intentionally restrict postoperative weightbearing in the majority of non-hip fractures, yet are content with unrestricted weightbearing following operations for hip fractures.